Towards precise synthetic neural codes: high-dimensional stimulation with flexible electrodes - Robin Kim; Yuxuan Liu; Jiaao Zhang; Chong Xie; Lan Luan (npj Flexible Electronics)
Abstract Neural representations arise from high-dimensional population activity, but current neuromodulation methods lack the precision to write information into the central nervous system at this complexity. In this perspective, we propose high-dimensional stimulation as an approach to better approximate natural neural codes for brain-machine interfaces. Key advancements in resolution, coverage, and safety are essential, with flexible microelectrode arrays offering a promising path toward precise synthetic neural codes.